(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
The article contains results of the study of the historical herbarium «Flora of Japan» (KW) of japanologist, linguist, translator, intelligence officer O.L. Kletny who was repressed as political prisoner in 1938. The herbarium materials were collected in Tokyo (Japan) in 1914 and include 88 specimens of 84 species of 51 genera of 15 families of the flora of the Japanese islands. In the paper a brief biography of O.L. Kletny is given; the methods of collections study is discussed. An annotated list of all the species contained in the three thematic herbarium albums, named «Flora of Japan. Coniferous», «Flora of Japan. (Nihon-Sinrin). Hardwood trees. I», «Flora of Japan. Bamboo (Nihon-Take)» is presented.